Pagdikta (The dictation): the meanings in Filipino mothers’ experience of using herbal plants in the management of their children’s fever - Leocadio, Michael C.; Jabai, Alrajii C.; Rul, Jenylyn A.; Sanche, Louise Anne D.; Sauler, Rica Gertrude T.; Tan, Apple Mae A.; Tapispisa, Jopheth N. (Universiti Kebangsaan Malaysia, 2011)
One of the main indicators of an illness is fever and it is managed in different ways by mothers based on their existing culture. After a health diagnosis, dominant fever management of a certain community with inaccessible health center was the use of herbal plants despite easy access to relatively expensive over-the-counter medicine. Hence, we explored the meanings of using herbal plants in the management of children’s fever by Filipino using qualitative-phenomenological research philosophy (Colaizzi, ). Seven mothers were interviewed with the aid of recorders, journals, field notes and memos with the mothers’ consents. The narrative data were analyzed using the Morse and Field process. Themes were discovered highlighting the process of how the mothers managed their children’s fever through the utilization of herbal plants. Thematic variations in the use of herbal plants and their preparation, utilization and application were ascertained. From these thematic analysis emerged a cultural relationality which provided an integrated process of PAGDIKTA (Eng. dictation), the major theme of the experience. This summarized the selection, adoption and transfer of the herbal plants for management of fever with cultural involvement. PAGDIKTA [acronym which means PAG-pitas, DIK-dik, TA-pal] is the concept learned to present the views of cultural selection, adoption and transfer of fever management practice of motherinformants. PAGDIKTA can be further analyzed with the following subconcepts: Pagpitas (Eng. picking) is the process of choosing a culturally accepted herbal plant for their fever. Dikdik (Eng. pounding) is the progression of cultural adoptation and imbuement of practice by mother-informants. Tapal (Eng. application) is the application and transmission of the feverpractice based on the perceived and observed efficacy of practices directed to their children’s fever. Cultural awareness, assessment and competence are needed to completely understand specific populations with special needs such as the mothers in a community in the Philippines.